A sindemia da covid-19 em uma comunidade quilombola de Mato Grosso : repercussões e iniquidades em saúde - Madureira, Kleber Gonçalves (2023)
The term syndemic implies a complex network of social and economic factors, which, associated with the so-called Social Determinants of Health (SDH), promote and amplify the negative effects of interactions between diseases. With the aim of analyzing the repercussions of Covid-19 from the perspective of Quilombolas in a community in Mato Grosso from the perspective of the syndemic, the present study intends to answer the following question: what are the repercussions (material and symbolic) of the Covid-19 syndemic? 19 in a quilombola community in Mato Grosso? The study is of the qualitative type. The participants, quilombolas from a quilombo in Mato Grosso, who were intentionally selected through indication by the State CONAQ. As an instrument, the semi-structured thematic script was used and, as a data collection technique, the semi-structured interview. The source of the data were quilombolas from Mata-Cavalo and official and public documents, prepared by government agencies and independent institutions, on the pandemic and quilombola peoples. The data were treated by thematic analysis, seeking in the empirical material the expression of the syndemic as interconnections of biological and social elements, using the concepts of repercussions, health, iniquities and necropolitics, always in the context of inequalities and racism to also think about actions antiracists. The results were presented in six topics. It begins by characterizing the research subjects and bringing the impressions of the experience by visiting the place where precariousness in the infrastructure of the communities was verified, the roads, bumpy and without signs; lack of lighting and public transport and insufficient basic sanitation, in short, various precarious conditions that portray how the quilombolas of Mata Cavalo go through a process of abandonment and invisibilization by the public power. Then, the psychosocial repercussions of Covid-19 are presented, which due to the insufficiency of health services, vulnerability and aggression due to pre-existing cultural prejudices, were exacerbated in Mata Cavalo, causing them to live, in a particular way, a pandemonium, a atmosphere of tension, fear and horror. The fourth topic, the characterization of the syndemic, finds that Covid-19 is not a democratic disease and has its privileged, the black and poor population, those most exposed to the virus, hunger and death. That is, due to the interaction of biological and social processes, Covid-19 is not a purely biological phenomenon, common to all, but a syndemic in which conditions and states that have an impact on the health-disease process are combined and potentiated. The fifth topic highlights the precariousness of Primary Health Care, the strong investment in the private sector and the lack of health care experienced by the quilombolas of Mata Cavalo. Another aspect that stands out is the mobilization of knowledge from other therapeutic systems, which in itself is not problematic, on the contrary. However, it becomes so when imposed by the insufficiency of official health services and access problems as narrated by the interviewees. And finally, social (dis)protection, where the impoverishment of the quilombolas constitutes a strategy of domination and control, which keeps their bodies fixed in poverty. Social inequality that relegates blacks to the outskirts of consumption and existence, forcing them to abandon their lands and migrate to the urban environment in search of better living conditions. The results of this research showed that racism affected the way in which quilombolas experienced the Covid-19 syndemic, configuring unfavorable scenarios, deprivation of fundamental rights, which made it difficult, limited and prevented the search for care and access to essential services such as health, transportation, basic sanitation, food, employment and socioeconomic mobility.